2004
DOI: 10.1080/0950069042000243763
|View full text |Cite
|
Sign up to set email alerts
|

Primary teachers’ changing attitudes and cognition during a two‐year science in‐service programme and their effect on pupils

Abstract: Changes in 70 teachers' confidence, attitudes and science understanding were tested before and after a major in-service programme. Attitudes were assessed using a 49-item Likert-scale test that probed attitudes to practical science teaching and in-service training. Multi-choice and open-ended questions measured understanding of electricity; melting, dissolving and evaporation; forces; and investigations. Data on pupils' attitudes and cognition were also collected. After in-service, teachers' confidence about s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 21 publications
(33 reference statements)
2
72
0
10
Order By: Relevance
“…The studies addressed in this review underscore this observation. The majority of the studies provided no appropriate definition for the concept of attitude (Appleton, 1995, Appleton & Kindt, 1999Atwater et al, 1991;Carleton et al, 2008;Cobern & Loving, 2002;Coulson, 1992;Eurobarometer 38.1, 1992;Evans & Durant, 1995;Haney et al 1996;Harty et al, 1991;Hartshorne, 2008;Haury, 1989;Jarret, 1999;Jarvis & Pell, 2004;Johnston & Ahtee, 2006;Koballa, 1986;Liang & Gabel, 2005;Martin-Dunlop & Fraser, 2007;McDevitt et al, 1993;Mulholland & Wallace, 1996;Palmer, 2001Palmer, , 2004Pedersen & McCurdy, 1992;Ramey-Gassert et al, 1996;Shepardson & Pizzini, 1992;Yates & Goodrum, 1990;Yilmaz-Tuzun, 2007;Young & Kellogg, 1993;Young, 1998). Some of these studies gave a coarse definition of attitude without specifying the various dimensions of the construct.…”
Section: Critical Reflectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies addressed in this review underscore this observation. The majority of the studies provided no appropriate definition for the concept of attitude (Appleton, 1995, Appleton & Kindt, 1999Atwater et al, 1991;Carleton et al, 2008;Cobern & Loving, 2002;Coulson, 1992;Eurobarometer 38.1, 1992;Evans & Durant, 1995;Haney et al 1996;Harty et al, 1991;Hartshorne, 2008;Haury, 1989;Jarret, 1999;Jarvis & Pell, 2004;Johnston & Ahtee, 2006;Koballa, 1986;Liang & Gabel, 2005;Martin-Dunlop & Fraser, 2007;McDevitt et al, 1993;Mulholland & Wallace, 1996;Palmer, 2001Palmer, , 2004Pedersen & McCurdy, 1992;Ramey-Gassert et al, 1996;Shepardson & Pizzini, 1992;Yates & Goodrum, 1990;Yilmaz-Tuzun, 2007;Young & Kellogg, 1993;Young, 1998). Some of these studies gave a coarse definition of attitude without specifying the various dimensions of the construct.…”
Section: Critical Reflectionsmentioning
confidence: 99%
“…The remaining studies, which did not use the STEBI, had devised their own surveys and questionnaires on self-efficacy (Appleton, 1995;Jarvis & Pell, 2004;Skamp, 1991) or questionnaires on self-confidence (Harlen & Holroyd, 1997;Holroyd & Harlen, 1996;Murphy et al, 2007). Many of the instruments used in these studies were neither validated nor reported reliability measures (Appleton, 1995;Hoslroyd & Harlen, 1996;Skamp, 1991).…”
Section: Self-efficacy As Shown Inmentioning
confidence: 99%
See 3 more Smart Citations